Uso de adjuvante siliconado em substituição total ou parcial do óleo mineral na aplicação de fungicidas em soja e milho - Güths, Guilherme (2013)
Soybean and corn are two of the most important commodities in Brazilian agribusiness. However these crops are infected by many diseases, including rusts, which reduce plant yield. Such diseases are mainly controlled by fungicides applied along the season in mixes with adjuvants made of mineral or vegetal oils, silicon, and other compounds. In this research we evaluate the performance of fungicide + adjuvants mixes on the control of diseases in field trials with soybean (2012 and 2013) and corn (2012). We use the fungicides Priori Xtra (cyproconazol + azoxystrobin, 0.3 L.ha-1) in 2012 and 2013, and Elatus (azoxystrobin + solatenol, 0.25 L.ha-1) in 2013. The adjuvants were Nimbus (mineral oil, at 0.3 or 0.6 L.ha-1) and Break-Thru (organic-silicon, various rates). All trials were organized in randomized block with four replicates. In 2012 the soybean cultivar was BMX Apolo RR, and the corn hybrids Pioneer 30F53H and Dekalb 240. For both soybean and corn the addition of Break-Thru at 0.2 or 0.25 L.ha-1 to Priori Xtra provided disease control and grain yield similar to or better Nimbus at 0.6 L.ha-1. In 2013 we used the soybean cultivars BMX Apolo RR and BMX Ativa RR in single or mixed plantings (alternated rows). The rate reduction of Nimbus to 0.3 L.ha-1 did not affect fungicide performance when it was supplemented with Break-Thru at 0.07 L.ha-1 or higher. Elatus provided better rust control and grain yield than Priori Xtra. The mixed plantings did not influence disease occurrence and grain yield over the single ones